Application of Management Control System in Commercial Bank in Nepal - Singh, Prem Bahadur (Brixton Scholarly Review, 2025)
The application of Management Control Systems (MCS) in Nepali commercial banks is crucial for enhancing operational efficiency and ensuring regulatory compliance. This study examines the design and implementation of MCS within this sector, highlighting the significance of tailored training programs, stakeholder engagement, and the integration of global best practices. By adopting a robust MCS, banks can effectively monitor performance, manage risks, and align their strategic objectives with operational activities. The research emphasizes the need for continuous improvement and adaptation of MCS to meet the evolving challenges of the financial landscape in Nepal. Ultimately, a well-implemented MCS not only drives performance but also contributes to the stability and growth of the banking sector, fostering a resilient financial system in the region.